2012
DOI: 10.3766/jaaa.23.6.7
|View full text |Cite
|
Sign up to set email alerts
|

The Ear Is Connected to the Brain: Some New Directions in the Study of Children with Cochlear Implants at Indiana University

Abstract: Since the early 1980s, the DeVault Otologic Research Laboratory at the Indiana University School of Medicine has been on the forefront of research on speech and language outcomes in children with cochlear implants. This paper highlights work over the last decade that has moved beyond collecting speech and language outcome measures to focus more on investigating the underlying cognitive, social, and linguistic skills that predict speech and language outcomes. This recent work reflects our growing appreciation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 95 publications
1
28
0
Order By: Relevance
“…Fortunately, the recent implementation of mandatory hearing screening for all newborns, rather than only those with risk factors for hearing loss, has meant these children are now often identified shortly after birth, so treatment can begin early. Evidence from several investigators has reliably shown that the early initiation of both medical interventions, especially cochlear implantation (CI), and behavioral interventions can substantially ameliorate delays in language learning imposed by congenital hearing loss (Geers & Nicholas, 2013; Houston et al 2012; Moeller, 2000; Ramos-Macías, Borkoski-Barreiro, Falcón-González, & Plasencia, 2014; Robbins, Osberger, Miyamoto, & Kessler, 1995). Nonetheless, mean performance of these children remains below that of children with normal hearing (NH) (Geers & Hayes, 2011; Spencer & Tomblin, 2009; Tobey et al, 2013) and gaps exist in our understanding of why that is.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the recent implementation of mandatory hearing screening for all newborns, rather than only those with risk factors for hearing loss, has meant these children are now often identified shortly after birth, so treatment can begin early. Evidence from several investigators has reliably shown that the early initiation of both medical interventions, especially cochlear implantation (CI), and behavioral interventions can substantially ameliorate delays in language learning imposed by congenital hearing loss (Geers & Nicholas, 2013; Houston et al 2012; Moeller, 2000; Ramos-Macías, Borkoski-Barreiro, Falcón-González, & Plasencia, 2014; Robbins, Osberger, Miyamoto, & Kessler, 1995). Nonetheless, mean performance of these children remains below that of children with normal hearing (NH) (Geers & Hayes, 2011; Spencer & Tomblin, 2009; Tobey et al, 2013) and gaps exist in our understanding of why that is.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that deaf children with CIs have difficulties with domain-general cognitive control processes (Beer, Kronenberger, & Pisoni, 2011; Beer, Pisoni, & Kronenberger, 2009; Houston et al, 2012; Pisoni, Conway, Kronenberger, Henning, & Anaya, 2010). It is therefore possible that delays with domain-general cognitive control abilities—that is, cognitive control abilities that cut across different cognitive functions and processes rather than being specific to language—negatively affect the ability of deaf children with CIs to successfully use sentence context to help understand spoken language, over and above any difficulties they may have due to lack of experience hearing and using spoken language itself.…”
mentioning
confidence: 99%
“…Also important to consider are potential differences in the neural health of surviving auditory nerve fibers in the two ears. It is also likely that, while the auditory measures are stable over repeated trials, the task engaged specific aspects of executive function that contributed to the results, including individual differences in the ability to inhibit interfering information, switch and/or sustain attention on the task, or other factors such as working memory[32, 33]. The data in this paper do not provide sufficient evidence to directly answer these questions.…”
Section: Resultsmentioning
confidence: 89%